2019
DOI: 10.3390/su11020456
|View full text |Cite
|
Sign up to set email alerts
|

Wild Plants Potentially Used in Human Food in the Protected Area "Sierra Grande de Hornachos" of Extremadura (Spain)

Abstract: Natura 2000 is a network of protected spaces where the use of natural resources is regulated through the Habitat Directive of the European Union. It is essential for the conservation of biodiversity in Europe, but its social perception must be improved. We present this work as a demonstration case of the potentialities of one of these protected areas in the southwest (SW) Iberian Peninsula. We show an overview of the catalog of native wild plants of the place, which have nutritional and edible properties, havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…These climatic and geographical characteristics allow the existence of an abundant fauna (with more than 220 vertebrates) and plant diversity, which, according to recent surveys, could exceed 1300 species [14].…”
Section: The Study Area: Sierra Grande De Hornachosmentioning
confidence: 99%
See 2 more Smart Citations
“…These climatic and geographical characteristics allow the existence of an abundant fauna (with more than 220 vertebrates) and plant diversity, which, according to recent surveys, could exceed 1300 species [14].…”
Section: The Study Area: Sierra Grande De Hornachosmentioning
confidence: 99%
“…The presence of interculturality persists in the gastronomy of the inhabitants of Hornachos, fundamentally that of the so-called Moors, of which the Moorish orchards are still preserved, and where planting techniques and knowledge have endured, as well as native varieties of enormous genetic, cultural, and commercial value [14]. This is, therefore, a territory with a rich cultural and agro-environmental heritage; however, this complexity has not been expressed in opportunities for the dynamization of the local economy and the creation of bonds of a union in the community.…”
Section: The Study Area: Sierra Grande De Hornachosmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of EBR usage is due to differences in culture and differences in traditional knowledge between minority groups [24], but conserving EBRs is critical to maintaining both ecosystem biodiversity and cultural diversity. In efforts to increase EBR conservation, researchers around the world have identified different types of EBRs [32,33], the intensity of EBR utilization [28,34], and human behavior surrounding EBR use and have gathered other related information [35,36]. Research has revealed the pressure on local biodiversity from the consumption behavior of local inhabitants [34] as researchers try to understand the driving forces of EBR consumption [20,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning the work by Blanco-Salas et al [8] on classification and cataloguing of wild plants potentially used in human food in the protected area Sierra Grande de Hornachos of Extremadura in Spain, that gives an example of how botany knowledge can effectively promote development, enhancement of territories, and biodiversity preservation, by guiding tourism and consumers towards an haute cuisine, new gastronomy, and environment-friendly recipes.…”
Section: Introductionmentioning
confidence: 99%